2020
DOI: 10.3390/ijerph17030920
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Body Mass Index and Leisure-Time Physical Activity in Adults with Multiple Sclerosis

Abstract: (1) Purpose: Conflicting information exists regarding the relationship between obesity, leisure-time physical activity (PA), and disability in people with multiple sclerosis (PwMS). We aimed to investigate the association between leisure-time PA and weight status in a relatively large cohort of PwMS. Furthermore, we examined this relationship according to the level of neurological disability. (2) Methods: The study included 238 PwMS (138 women) with a mean Expanded Disability Status Scale (EDSS) score of 2.5 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Our findings showed no difference in physical engagement among participants with different EDSS scores. This finding supports previous data from our center that showed no relation between physical activity and obesity, as measured by BMI in 238 individuals with MS with a mean ± SD EDSS score of 2.5 ± 1.7 [30].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings showed no difference in physical engagement among participants with different EDSS scores. This finding supports previous data from our center that showed no relation between physical activity and obesity, as measured by BMI in 238 individuals with MS with a mean ± SD EDSS score of 2.5 ± 1.7 [30].…”
Section: Discussionsupporting
confidence: 92%
“…The female-to-male ratio of MS patients who participated in our study was calculated to be 2.3/1, consistent with the incidence rate of female-to-male MS, which is 2.5/1 worldwide (11). In a survey conducted with 238 MS patients comparing body mass index and physical activity and examining the impact of this relationship on neurological disability, no relationship was found between physical activity level and BMI or between obesity and neurological disability (12). In our study, although no statistically significant difference was found in the measurements of BMI, neck and shoulder circumference, and fathom length between MS patients and healthy subjects, the mean chest circumference was statistically significantly higher in MS patients than in healthy subjects.…”
Section: Discussionsupporting
confidence: 79%
“…Regardless of the method, no associations were found between obesity and level of disability in the cohort. 1 These findings are in agreement with a previous 24-month study that BMI was not predictive of disability in a sample of 269 people with relapsing-remitting MS. 2 Similarly, Lambert et al. 3 reported an absence of any association between disability and weight status in a group of people with mild-moderate MS.…”
supporting
confidence: 92%